Liraglutide suppresses obesity and promotes browning of white fat via miR-27b in vivo and in vitro. Issue 11 (November 2021) - Wang, Xing; Chen, Shuchun; Lv, Dan; Li, Zelin; Ren, Luping; Zhu, Haijiao; Xie, Xing; Liu, Yang
Objective: To investigate the effect of liraglutide on the browning of white fat and the suppression of obesity via regulating microRNA (miR)-27b in vivo and in vitro . Methods: Sprague-Dawley rats were fed a high-fat (HF) diet and 3T3-L1 pre-adipocytes were differentiated into mature white adipocytes. Rats and mature adipocytes were then treated with different doses of liraglutide. The mRNA and protein levels of browning-associated proteins, including uncoupling protein 1 (UCP1), PR domain containing 16 (PRDM16), CCAAT enhancer binding protein β (CEBPβ), cell death-inducing DFFA-like effector A (CIDEA) and peroxisome proliferator-activated receptor-γ-coactivator 1α (PGC-1α), were detected using quantitative real-time polymerase chain reaction and Western blotting. Results: Liraglutide decreased body weight and reduced the levels of blood glucose, triglyceride and low-density lipoprotein cholesterol in HF diet-fed rats. Liraglutide increased the levels of UCP1, PRDM16, CEBPβ, CIDEA and PGC-1α in vivo and vitro . The levels of miR-27b were upregulated in HF diet-fed rats, whereas liraglutide reduced the levels of miR-27b. In vitro, overexpression of miR-27b decreased the mRNA and protein levels of UCP1, PRDM16, CEBPβ, CIDEA and PGC-1α. Transfection with the miR-27b mimics attenuated the effect of liraglutide on the browning of white adipocytes. Conclusion: Liraglutide induced browning of white adipose through regulation of miR-27b.